Analysis Through Composition: Principles of the Classical Style - Cook, Nicholas (Oxford Oxford university press, 1996)
In this textbook Professor Nicholas Cook provides an unusual and stimulating approach to teaching analytical concepts through the study of style composition. The emphasis is on analysis and decision-making within a practical context, drawing on `real' musical examples ranging from J. C. Bach to early Beethoven. Students can use these examples as models to complete compositional assignments provided in a number of subject areas. The illustrative use of contemporary source materials such as sketches and pedagogical exercises (e.g. Thomas Attwood's studies with Mozart) provides a useful historical framework and draws together an appealing combination of musical disciplines